Development of STEM-Based Physics Learning Media Materials on Temperature and Heat to Improve Students' Mastery of Concepts - Aris Doyan; Muh Makhrus; Ayu Safitri Melita (Jurnal Penelitian Pendidikan IPA, 2023)
The research conducted in this development is aimed at producing STEM-based learning media products in physics subjects, especially in temperature and heat materials to improve students' mastery of concepts that are valid, practical, and effective. The design of this study uses a 4D model in the form of Design, Define, Disseminate, and Development. With STEM-based learning media in the form of a digital calorimeter as a product being developed. Test instruments, validation sheets, and response questionnaires were used as data collection techniques. Evaluation of product validity was carried out by three media experts and material experts and used Aiken-V as a method of analysis. The practicality of the product is analyzed using the practicality test while the effectiveness is obtained by increasing students' mastery of concepts with Â¬N-gain. The results of the validator's assessment of the digital calorimeter media showed an average result of Aiken-V of 0.94 which was very valid. The average results for the practicality assessment of the developed media can be seen from the student response questionnaire which shows a value of 4.51 in the fairly practical category. The average result for the effectiveness of the developed media can be seen from the increase in mastery of the concept, which is equal to 0.60 with high criteria. So it can be concluded that STEM-based physics learning media to improve students' mastery of concepts is valid, practical, and effective